2011
DOI: 10.1143/jjap.50.095002
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method of Synthesizing Nickel–Nitrilotriacetic Acid Gold Nanoparticles with a Narrow Size Distribution for Protein Labeling

Abstract: We developed a simple method to synthesize nickel–nitrilotriacetic acid gold nanoparticles (Ni–NTA Au NPs) with a narrow size distribution for site-specific labeling in protein complexes. Au NPs were synthesized by the reduction of HAuCl4 using trisodium citrate and tannin acid. Then, the nanoparticle surfaces were modified with NTA and subsequent complexation with Ni2+. The mean diameter of the synthesized Ni–NTA Au NPs was 4.3 nm, and the coefficient of variation was 9%. The specific binding of the Ni–NTA Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…p150 mutants carry the His-tag at respective locations: the N-and C-termini of p150, both sides and the hinge of CC1, and both sides of CC2 (Figure 2A, Figure 1-S1). The efficiency and specificity of nanogold labeling of the human dynactin used in this study has been reported previously (Kitai et al, 2011).…”
Section: Localization Of the N-and C-termini Of The P150 Subunitmentioning
confidence: 72%
See 2 more Smart Citations
“…p150 mutants carry the His-tag at respective locations: the N-and C-termini of p150, both sides and the hinge of CC1, and both sides of CC2 (Figure 2A, Figure 1-S1). The efficiency and specificity of nanogold labeling of the human dynactin used in this study has been reported previously (Kitai et al, 2011).…”
Section: Localization Of the N-and C-termini Of The P150 Subunitmentioning
confidence: 72%
“…A streptavidin binding peptide (SBP) was fused to one of the subunits (Figure 1-S1) and all the other subunit components of the dynactin complex were co-purified by affinity chromatography (Figure 1-S2). We firstly used a complex including recombinant p62 (SBP-p62 in Figure 1-S1), which locates at the pointed end of the Arp1 rod (Kitai et al, 2011;Schafer et al, 1994), to obtain an intact form of the dynactin sidearm. The negative stain EM images revealed the sidearm complex projecting from one end of the Arp1 rod ( Figure 1A; Figure 1-S3A, left).…”
Section: Em Images Of the Dynactin Complex Revealed The Flexibility Omentioning
confidence: 99%
See 1 more Smart Citation
“…42 The responsive self-assembly characteristics of Au-S4E8Gs are based on the thermally reversible conformational switching in the elastin-like block between the hydrophilic random coil conformation and the hydrophobic β-spiral adopting repetitive type II β-turns. 2628,31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…3941 The synthesis strategy following the method reported by Kitai et al 42 and is shown in Figure S2. The XPS characterization of the Au NPs at various steps of the reaction is summarized in Figure S3.…”
Section: Results and Discussionmentioning
confidence: 99%